A coalitional game‐based relay load balancing and power allocation scheme in decode‐and‐forward cellular relay networks. Issue 9 (8th May 2015) - Farazmand, Yalda; Alfa, Attahiru S.
Abstract: In this paper, a game theoretic relay load balancing and power allocation scheme is proposed for downlink transmission in a decode‐and‐forward orthogonal frequency division multiple access‐based cellular relay network. A system with a base station communicating with multiple users via multiple relays is considered. The relays have limited power, which must be divided among the users they support. In traditional scheme, each relay simply divides its transmit power equally among all its users. Moreover, each user selects the relay with the highest channel gain. In this work, we do not apply the traditional relay scheme. It is because the users are distributed randomly, and by applying the traditional relay selection scheme, it may happen that some relays have more users connected to them than other relays, which results in having unbalanced load among the relays. In order to avoid performance degradation, achieve relay load balancing, and maximize the total data rate of the network, a game theoretic approach is proposed, which efficiently assigns the users to relays. The power of each relay is wisely distributed among users by the efficient power allocation scheme. Simulation results indicate that the proposed game‐based scheme can considerably improve the average sum‐spectral efficiency. Moreover, it shows that by applying the game, users who can connect to uncongested relays join them as opposed to connecting to congested relays. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, a game theoretic relay load balancing and power allocation approach is proposed for downlink transmission in decode‐and‐forward cellular relay networks. Relays have limited power that must be divided among the users they support. Moreover, in order to avoid performance degradation due to relay overloading, the relay load balancing scheme is considered.